The Development And Effectiveness Of A PjBL Speaking Module In Enhancing English Speaking Proficiency And Learner Autonomy Among Efl Undergraduates In China - Wang, Juan (2024)
The study examined the effectiveness of a PjBL speaking module on English-speaking proficiency (ES) and learner autonomy (LA). Following the “analysis, design, develop, implement, and evaluate” (ADDIE) module outlined by Branch (2009), the project-based learning (PjBL) speaking module integrated the gold standards for PjBL (GSPjBL) as proposed by Larmer et al. (2015) into the English as a foreign language (EFL) learning material. The study employed a quasi-experiment by purposively selecting 35 second-year undergraduates for the experimental group who had experienced the PjBL speaking module. In comparison, the control group comprised 35 second-year undergraduates who received traditional speaking module. The experimental and the control groups were on two campuses of a university respectively in China. Mixed methods were used to collect data through ES pre and post-test, LA pre- and post-questionnaire, and semi-structured interviews. The ANCOVA results showed that students’ vocabulary and grammar proficiency in the experimental group were significantly higher than those in the control group. At the same time, there was no significant difference between the experimental and control groups in post-pronunciation mean scores.